Energy conservation in distribution network using algorithms (Fruit Fly Algorithm and Ant Lion Algorithm) by reducing power loss - Mani, Iswariya; Thangaraj, Yuvaraj (AIP conference proceedings, 2023)
The purpose of this article is to compare and contrast two new algorithms, Fruit Fly Algorithm and Ant Lion Algorithm, for energy savings in the Distribution Network through optimal DSTATCOM allocation. Materials and Methods: Two algorithms, Fruit Fly Algorithm and Ant Lion Algorithm, are used to distribute DSTATCOM data. Results: ALO has a power loss reduction of (140.58 KW) based on the collected data, while FFA has a power loss reduction of (35173 $) and AL has a savings of (32765 $). To sum up, FFA offers superior energy savings (conservation) than ALO based on the given facts.